Digital Leadership Strategies in Public Health Transformation: A Systematic Review of the Literature on Multi-Level Governance Practices, Inequalities, and Policies - Fidi Mustafa; Asna Aneta; Yanti Aneta (Departemen Administrasi Publik, Universitas Diponegoro, 2026)
The digital transformation of public health systems has created an urgent need to reexamine leadership roles and strategies amidst the dynamics of multi-level governance and increasing digital inequality. This study aims to identify patterns, challenges, and strategic contributions of digital leadership in the complex context of public health policy.A Systematic Literature Review (SLR) approach was used following the PRISMA 2020 guidelines. A total of 96 articles from seven international databases were screened, and 18 selected articles were thematically analyzed using the Braun & Clarke method. The analysis focused on three main dimensions: leadership style, multi-level governance context, and digital equity in public services.The results reveal three key findings: first, current digital leadership tends to be technocratic and insufficiently responsive to inequalities in digital access and literacy. Second, a policy paradox exists between the central and local levels, creating obstacles to strategic implementation. Third, ethics and public justice have not been explicitly underpinned in the design of digital leadership strategies. Based on these three findings, a conceptual model was developed based on the intersection of ethical digital leadership, cross-level governance, and sensitivity to digital inequality.This research contributes to the development of a more reflective and applicable theory of public sector leadership, and offers policy direction and training for justice-based digital leadership.